When Money Can’t Be Avoided: Helping Money Avoidant Widows Using the Changes and Grief Model (FTA Best Paper Award) - Deb Finnegan Biever; Nipa Patel; Ashley Agnew; Daniel Kopp; Jodi Krausman; Megan A McCoy (Journal of Financial Therapy, 2021)
Widows represent one of the fastest-growing demographics due to the global COVID-19 pandemic. Many widows also lost their family’s financial manager because more men hold the role of household financial manager. When their spouse dies, the widow can experience unhealthy attitudes towards finances and financial anxiety. The Changes and Grief Model for Financial Guidance pairs financial therapy techniques and inquiry methods, such as The Work of Byron Katie®, with the grief process and the change cycle. Using this model enables financial practitioners, mental health practitioners, and financial therapists to recognize the stage of grief the widow is experiencing and use the proper financial therapy modalities to support the money-avoidant widow. The model presented will provide the process to deepen client relationships through meaningful communication while compassionately supporting money-avoidant widows through financial decisions during the difficult initial stages of grief.
Keywords: changes and grief model; financial anxiety; grief; household financial manager; money avoidant; widow